A.C. Cuza, German Antisemitism, and the Swastika - BLASEN, Philippe Henri (Studia Universitatis Babeș-Bolyai Historia, 2022)
This case study of transnational antisemitism in the 1910s and 1920s argues that the Romanian antisemite A.C. Cuza (1857-1947) copied the swastika from the German antisemite Heinrich Kraeger (1870-1945). It examines the evolution of Cuza’s political antisemitism from the 1890s until 1923 and discusses the possible origins of Cuza’s use of the swastika and his interpretations of the symbol. It highlights that Cuza used various foreign sources to produce vague and contradictory interpretations of the swastika, that he made no effort to give it a coherent racial meaning, and that he opportunistically but inconsistently tried to Christianise it. The study concludes that the swastika in his view became both a German and a Romanian ethnic symbol, performing the same antisemitic function in each context. Article history: Received 25.05.2022; Revised: 26.07.2022; Accepted: 26.07.2022; Available online: 15.09.2022 Rezumat: Acest studiu de caz de antisemitism transnațional în anii 1910-1920 susține teoria că A.C. Cuza (1857-1947) a copiat svastica de la antisemitul german Heinrich Kraeger (1870-1945). Articolul examinează evoluția antisemitismului politic dezvoltat de Cuza între anii 1890 şi 1923 şi discută posibilele origini ale utilizării svasticii de către Cuza şi ale interpretărilor pe care le-a dat acestui simbol. Articolul subliniază că A.C. Cuza a folosit diverse surse străine pentru a produce interpretări vagi şi contradictorii ale svasticii; că nu a făcut niciun efort pentru a-i da un conținut semantic rasial coerent şi că, în mod oportunist şi inconsistent, a încercat să o creştineze. Articolul conclude că, în viziunea lui Cuza, svastica a devenit un simbol etnic în acelaşi timp german şi român, având aceeaşi funcție antisemită în fiecare dintre aceste contexte. Cuvinte cheie: Antisemitism politic; antisemitism studențesc; naționalism român; transnaționalism; Liga Apărării Naționale Creştine; Garda de Fier